Terapia fotodinâmica antimicrobiana com fenotiazínicos: ensaios in vitro em staphylococcus aureus - Vergilio, Katia Lumi Tanikawa (2020)
Staphylococcus aureus is associated with acquired infections, considered one of the main human pathogens, due to its easy dissemination and resistance to antibiotics. Antimicrobial photodynamic therapy (aPDT) uses a light source in combination with a photosensitizer (FS) to induce a phototoxic reaction, producing reactive oxygen species that can destroy lipids and proteins causing cell death. The effect of aPDT is related to several physical, chemical and biological properties specific to FS. Phenothiazine dyes show high absorption in the red region of the electromagnetic spectrum (600–680 nm). Studies evaluating the action of FS Azure A (AA), Azure B (AB) and Dimethyl methylene blue (DMAM) compared to methylene blue (AM), in addition to establishing the relationship between the effectiveness and aggregation of compounds (metachromaticity ), may suggest new strategies to increase the effectiveness of aPDT. The purpose of this study was to compare the effectiveness of antimicrobial photodynamic therapy with phenothiazines in reducing in vitro growth of S. aureus. Colony-forming units were determined for each FS tested in different concentrations and the samples were also submitted to aPDT treatment (11.2mW / cm2, 4.7 J / cm2 for 7 minutes) using the 660nm LED system (BioLambda®, Brazil ). The incorporation evaluation was performed in quantification tests by spectrophotometry of the FS in S. aureus. In all analyzes, the data were subjected to the Kruskall-Wallis non-parametric test and the comparison between the means was performed by the Student- Newman-Keuls test, through the Biostat program, and considering a global level of significance of 95% ( α = 0.05). Among the phenothiazines tested in this study, DMAM showed the best results, with better bacterial cell incorporation, contributing to the cellular binding and intracellular dispersion in S. aureus, and effective antimicrobial action, in addition to demonstrating intense light absorption in the excitation wavelength lower concentration range, ensuring the possibility of toxicity to humans.